Host alkaloids differentially affect developmental stability and wing vein canalization in cactophilic Drosophila buzzatii - Padro, Julian (2014)
Host shifts cause drastic consequences on fitness in cactophilic species of Drosophila. It has been argued that changes in the nutritional values accompanying host shifts may elicit these fitness responses, but they may also reflect the presence of potentially toxic secondary compounds that affect resource quality. Recent studies reported that alkaloids extracted from the columnar cactus Trichocereus terscheckii are toxic for the developing larvae of Drosophila buzzatii. In this study, we tested the effect of artificial diets including increasing doses of host alkaloids on developmental stability and wing morphology in D. buzzatii. We found that alkaloids disrupt normal wing venation patterning and affect viability, wing size and fluctuating asymmetry, suggesting the involvement of stress–response mechanisms. Theoretical implications are discussed in the context of developmental stability, stress, fitness and their relationship with robustness, canalization and phenotypic plasticity.